Konflik Pasir Besi: Pro dan Kontra Rencana Penambangan Pasir Besi di Kabupaten Kulon Progo - Astuti, Eka Zuni Lusi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2012)
The policy made by the Local Government of Kulon Progo District toward pig iron mining is rejected by the people of coastal area. Consequences, it accelerated the social tension and created a social conflicts. It has arisen as a result of difference interest between the local government and the local people in terms of natural recourses management of coastal area. This research as qualitative research aims to observe the unique of âPasir Besi Conflictâ. And, the type of predatory regime in this issue has strong exaggerated the conflict into horizontal and vertical conflict.